Immunolocalization of pectic polysaccharides during abscission in pea seeds (Pisum sativum L.) and in abscission less def pea mutant seeds - Lee, Y.K.; Ayeh, K.O.; Ambrose, M.; Hvoslef-Eide, A.K. (BioMed Central Ltd., 2016)
Background: In pea seeds (Pisum sativum L.), the presence of the Def locus determines abscission event between its funicle and the seed coat. Cell wall remodeling is a necessary condition for abscission of pea seed. The changes in cell wall components in wild type (WT) pea seed with Def loci showing seed abscission and in abscission less def mutant peas were studied to identify the factors determining abscission and non-abscission event. Methods: Changes in pectic polysaccharides components were investigated in WT and def mutant pea seeds using immunolabeling techniques. Pectic monoclonal antibodies (1 → 4)-β-d-galactan (LM5), (1 → 5)-α-l-arabinan(LM6), partially de-methyl esterified homogalacturonan (HG) (JIM5) and methyl esterified HG (JIM7) were used for this study. Results: Prior to abscission zone (AZ) development, galactan and arabinan reduced in the predestined AZ of the pea seed and disappeared during the abscission process. The AZ cells had partially de-methyl esterified HG while other areas had highly methyl esterified HG. A strong JIM5 labeling in the def mutant may be related to cell wall rigidity in the mature def mutants. In addition, the appearance of pectic epitopes in two F3 populations resulting from cross between WT and def mutant parents was studied. As a result, we identified that homozygous dominant lines (Def/Def) showing abscission and homozygous recessive lines (def/def) showing non-abscission had similar immunolabeling pattern to their parents. However, the heterogeneous lines (Def/def) showed various immunolabeling pattern and the segregation pattern of the Def locus. Conclusions: Through the study of the complexity and variability of pectins in plant cell walls as well as understanding the segregation patterns of the Def locus using immunolabeling techniques, we conclude that cell wall remodeling occurs in the abscission process and de-methyl esterification may play a role in the non-abscission event in def mutant. Overall, this study contributes new insights into understanding the structural and architectural organization of the cell walls during abscission.
Keywords: Abscission; Def mutant; Immunolocalization; Pea (Pisum sativum L.); Pectic polysaccharide